Revised Estimates for the Number of Human and Bacteria Cells in the Body - Sender, Ron; Fuchs, Shai; Milo, Ron (PLOS Biology, 2016)
Thoroughly revised estimates show that the typical adult human body consists of about 30 trillion human cells and about 38 trillion bacteria.